Utilization of organic waste - Mansor, Mariatul Fadzillah (2021)
Waste is unwanted or unusable materials, any substance which is discarded after primary use, or is worthless, defective and of no use. Many different types of waste are generated, including municipal solid waste, agricultural and animal waste, medical waste, radioactive waste, hazardous waste, industrial non-hazardous waste, construction and demolition debris, extraction and mining waste, oil and gas production waste, fossil fuel combustion waste, etc. In general, it is divided into inorganic and organic waste.